An Assessment of The Opportunities for Entry into The Market for The Manufacturer of Promotional Products in Thailand - Somchatvong, Laddaporn (2009)
Given the expansion of promotional products industry worldwide for the past decades, this study assessed the attractiveness of the industry, specifically in Thailand, and identified the possibilities for new entrants into the market as manufacturers. Taking into account theories concerning industry analysis, barriers of entry and supplier selection processes, semi-structured interviews were conducted in order to evaluate the industry and identify opportunity to enter the market.